Reef fish identification tropical Pacific - Allen, Gerald R. (Jacksonville, Fla. New World, 2003)
A comprehensive field guide to tropical Pacific fishes with photographs of fish in their natural habitats ; "Includes Australia, Indonesia, Malaysia, Thailand, Vietnam, Philippines, Micronesia, Papua New Guinea; Solomon Islands, New Caledonia, Vanuatu, Fiji, Samoa, Tonga, French Polynesia, and beyond"--Cover
Keywords: Coral reef fishes -- Pacific Ocean -- Identification; Coral reef fishes -- Pacific Ocean -- Pictorial works